インド洋におけるゴンドワナ大陸初期分裂過程 - 羽入, 朋子; 野木, 義史; 藤井, 昌和; Tomoko, Hanyu; Yoshifumi, Nogi; Masakazu, Fujii (2017)
第8回極域科学シンポジウム/個別セッション：[OG] 極域地圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object